Tinjauan Yuridis Tindak Pidana Perdagangan Organ Tubuh Manusia untuk Transplantasi - Natalia Kristin; Enny Ristanti; Galih Puji Mulyono; Nahdiya Sabrina (Bhirawa Law Journal, 2022)
Technological advances are starting to make great progress in the world of health, especially for some diseases for which a cure has been found. For example, by seeking new treatments by transplanting several organs in the body. However, in practice the method of treatment with human organ transplantation is not easy to do, considering that the available organs are still very few compared to the needs of human organs. This causes the high price of human organs which should not be commercialized and many people take this opportunity to fulfill their financial needs by trading human organs. One of the laws that prohibits organ trafficking is Law Number 21 of 2007 concerning Eradication of the Crime of Trafficking in Persons. The provisions regarding the prohibition are contained in the formulation of Article 2, Article 3, Article 4, Article 5, Article 6, and Article 7 in the law.